2003
DOI: 10.1161/01.cir.0000062646.09566.cc
|View full text |Cite
|
Sign up to set email alerts
|

Vasopeptidase Inhibitor Omapatrilat Induces Profound Insulin Sensitization and Increases Myocardial Glucose Uptake in Zucker Fatty Rats

Abstract: Background-ACE inhibitors (ACEIs) improve insulin resistance and prevent type 2 diabetes, possibly mediated by inhibition of bradykinin (BK) degradation. The vasopeptidase inhibitor omapatrilat (OMA) raises BK to a greater extent than ACEIs by dual enzyme inhibition, whereas its insulin-sensitizing effects and mechanisms have not been investigated. Methods and Results-We compared the insulin-sensitizing effects of OMA, ramipril (an ACEI), losartan (an angiotensin II type 1 receptor blocker), and placebo by 2-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Nevertheless, the possibility cannot be excluded that candoxatril reduced endogenous GIP degradation in vivo, which contributed to the antihyperglycaemic effect, particularly when DPP-IV was simultaneously inhibited. There is also evidence that bradykinin is degraded by NEP [38], and several studies have shown that selective NEP or dual NEP/ACE (vasopeptidase) inhibitors lead to improved insulin sensitivity in obese, insulin-resistant rats [39][40][41][42] via a mechanism involving increased activation of the kinin-nitrous oxide pathway [39,42]. This improvement in whole-body insulin-mediated glucose disposal, effected by NEP inhibition, seemed to be a result of improvements in insulin sensitivity rather than secondary to changes in cardiovascular or renal function, because heart rate, blood pressure, femoral blood flow and GFR were unaltered [40,43].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the possibility cannot be excluded that candoxatril reduced endogenous GIP degradation in vivo, which contributed to the antihyperglycaemic effect, particularly when DPP-IV was simultaneously inhibited. There is also evidence that bradykinin is degraded by NEP [38], and several studies have shown that selective NEP or dual NEP/ACE (vasopeptidase) inhibitors lead to improved insulin sensitivity in obese, insulin-resistant rats [39][40][41][42] via a mechanism involving increased activation of the kinin-nitrous oxide pathway [39,42]. This improvement in whole-body insulin-mediated glucose disposal, effected by NEP inhibition, seemed to be a result of improvements in insulin sensitivity rather than secondary to changes in cardiovascular or renal function, because heart rate, blood pressure, femoral blood flow and GFR were unaltered [40,43].…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that reducing neprilysin activity may be beneficial via improving insulin secretion [4] and sensitivity [57]. …”
Section: Introductionmentioning
confidence: 99%
“…In another study, Arbin et al [30] observed that mixampril improves whole body insulinmediated disposal more effectively in animals with insulin resistance than in normal rats. The results obtained with mixampril were recently confirmed by a study using, in the same strain of rats, omapatrilat, another dual ACE/NEP inhibitor, and ramipril as ACE inhibitor [31]. All these studies clearly point out a role for kinins in the beneficial effect of ACE inhibitors on insulin sensitivity.…”
Section: Inhibition Of Ace Increase In Insulin Sensitivity and Kininsmentioning
confidence: 68%
“…In some studies, AT1 receptor antagonists have been reported to have no influence on insulin sensitivity [13,21,31,39], while in other works [40,41], these antagonists have been reported to improve glucose tolerance. Chronic administration of AT1 antagonist to insulin-resistant animals increased protein expression of GLUT-4, a glucose transporter, in muscle and myocardium [42].…”
Section: Inhibition Of Ace Increase In Insulin Sensitivity and Kininsmentioning
confidence: 99%